2012
DOI: 10.1128/cvi.00482-12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Immune Responses against a Wide Range of Mycobacterium tuberculosis Antigens in Patients with Active Pulmonary Tuberculosis

Abstract: e Characterizing host immune responses to molecular targets of Mycobacterium tuberculosis is essential to develop effective immunodiagnostics and better vaccines. We investigated the immune response against a large series of M. tuberculosis antigens, including 5 classical and 64 nonclassical (39 DosR regulon-encoded, 4 resuscitation-promoting factor [RPF], and 21 reactivation-associated) antigens in active-pulmonary-tuberculosis (TB) patients. Whole blood from TB patients (n ‫؍‬ 34) was stimulated in vitro wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 50 publications
4
58
1
1
Order By: Relevance
“…Combined, these results suggest that an Ag85-specific adaptive immune response primed by vaccination should be effective in the early stage of infection but of relative low value during the later stages of infection. In support of this, a recent study showed that in patients with active pulmonary TB, less than 25% of the patients responded to Ag85A/B proteins, and that these responses in general were very modest (8). In contrast, more than 70% of the patients responded to the early secretory antigenic target-6 and culture filtrate protein 10 (ESAT-6-CFP10) fusion protein and the TB10.4 protein with overall strong Agspecific responses.…”
mentioning
confidence: 71%
“…Combined, these results suggest that an Ag85-specific adaptive immune response primed by vaccination should be effective in the early stage of infection but of relative low value during the later stages of infection. In support of this, a recent study showed that in patients with active pulmonary TB, less than 25% of the patients responded to Ag85A/B proteins, and that these responses in general were very modest (8). In contrast, more than 70% of the patients responded to the early secretory antigenic target-6 and culture filtrate protein 10 (ESAT-6-CFP10) fusion protein and the TB10.4 protein with overall strong Agspecific responses.…”
mentioning
confidence: 71%
“…Further studies involving functional genomic analysis have shown, it as one of the highly expressed genes during the log phase growth of M. tb [13] and so far there are no notable immunological studies on this protein. The other selected antigen, Rv0753c is one of the reactivation proteins, which might be involved in reactivation of dormant M. tb to active form [14] and is also predicted as a probable methyl melonate semialdehyde dehydrogenase (mmsA) involved in the intermediate respiratory metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that Rpf are immunogenic in humans generating significant immune responses in both patients with active and latent disease (Chegou et al, 2012;Kassa et al, 2012;Riano et al, 2012). All Rpf proteins appear to be immunogenic with significant Tcell responses demonstrable in LTBI patients using interferon gamma release assays (IGRAs) (Commandeur et al, 2011;Geluk et al, 2014;Huang et al, 2013;Riano et al, 2012;Schuck et al, 2009).…”
Section: Rpf Expression In Human Infectionmentioning
confidence: 86%